2016
DOI: 10.1002/cssc.201600013
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Catalytic Conversion of Biobased Chemicals into Liquid Fuels in the Aqueous Phase

Abstract: Different biobased chemicals are produced during the conversion of biomass into fuels through various feasible technologies (e.g., hydrolysis, hydrothermal liquefaction, and pyrolysis). The challenge of transforming these biobased chemicals with high hydrophilicity is ascribed to the high water content of the feedstock and the inevitable formation of water. Therefore, aqueous-phase processing is an interesting technology for the heterogeneous catalytic conversion of biobased chemicals. Different reactions, suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
52
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 218 publications
(290 reference statements)
0
52
0
Order By: Relevance
“…(1)]. [3][4][5][6][7][8] The last oxygen atom in the ketone can be removed by hydrodeoxygenation via alcohol and olefin to producel inear alkanes, which can serve as fuels or lubricants. Furthermore, this reaction is highly suited for the selective removal of the oxygen content of chemical compounds because only one carbon atom is eliminated together with three oxygen atoms out of four.T his fact makes it particularly relevant for the upgrade of biomass-derived product mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…(1)]. [3][4][5][6][7][8] The last oxygen atom in the ketone can be removed by hydrodeoxygenation via alcohol and olefin to producel inear alkanes, which can serve as fuels or lubricants. Furthermore, this reaction is highly suited for the selective removal of the oxygen content of chemical compounds because only one carbon atom is eliminated together with three oxygen atoms out of four.T his fact makes it particularly relevant for the upgrade of biomass-derived product mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Lignocellulosic biomass is comprised of three primary components -cellulose, hemicellulose, and lignin -where each component has distinct characteristics and properties that allows it to be tailored to a unique purpose. 7 Furfural is a versatile chemical derived from pentosane-rich agricultural and forestry residues such as corn cobs, corn stover, saw dust, and straw.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the well‐known disadvantages of using homogeneous catalysts, and the wide use of solid base catalysts for these reactions there are few works dealing with the heterogeneously catalyzed cyclopentanone‐furfural condensation . In our previous work, preliminary results using Mg‐Zr mixed oxide as catalyst were reported, combining mild conditions (303–323 K) and aqueous media .…”
Section: Introductionmentioning
confidence: 99%
“…Hronec et al studied this reaction using homogeneous catalyst (NaOH), with more than 95% of the second adduct yield (C15) in less than 2 h. 13 Deng et al reported selectivities higher than 85% (in solid phase) after 2 h but working in solvent-free condensation and using NaOH as catalyst. 14 In spite of the well-known disadvantages of using homogeneous catalysts, 15 and the wide use of solid base catalysts for these reactions 7,16,17 there are few works dealing with the heterogeneously catalyzed cyclopentanone-furfural condensation. 18 In our previous work, preliminary results using Mg-Zr mixed oxide as catalyst were reported, combining mild conditions (303-323 K) and aqueous media.…”
Section: Introductionmentioning
confidence: 99%